2020
DOI: 10.1016/j.heliyon.2020.e05427
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic fitness and game performance indicators in professional football players; playing position specifics and associations

Abstract: The aim of this study was to identify associations between aerobic fitness (AF) and game performance indicator (GPI) in elite football. Participants were professional football players (males, n ¼ 16; age: 23.76 AE 2.64; body height: 181.62 AE 7.09 cm; body mass: 77.01 AE 6.34 kg). AF testing was conducted by direct measurement and included VO2max, running speed at aerobic threshold (AeT), and running speed at anaerobic threshold (AT). The GPI were collected by the position-specific performance statistics index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 32 publications
1
36
1
6
Order By: Relevance
“…In particular, analysis of soccer-specific positions revealed a strong correlation between AeT and low-intensity running (r = 0.78). On the other hand, other correlations analysed according to soccer-specific positions were not evidenced likely due to differences in AeT values and running performance among players in different positions, as demonstrated previously in a very recent study (Modric et al, 2020a).…”
Section: Aerobic Threshold and Match Running Performance In Soccersupporting
confidence: 58%
See 1 more Smart Citation
“…In particular, analysis of soccer-specific positions revealed a strong correlation between AeT and low-intensity running (r = 0.78). On the other hand, other correlations analysed according to soccer-specific positions were not evidenced likely due to differences in AeT values and running performance among players in different positions, as demonstrated previously in a very recent study (Modric et al, 2020a).…”
Section: Aerobic Threshold and Match Running Performance In Soccersupporting
confidence: 58%
“…However, elite soccer players spend the majority of match play performing low-intensity activities (e.g., standing, walking, jogging), while high-intensity efforts (e.g., high-speed running, sprinting) constitute approximately 10% of the total distance covered (Andrzejewski et al, 2016). Therefore, the energy used by soccer players is mainly produced by aerobic metabolism (Garcia-Tabar et al, 2019;Silva et al, 2011), so it is important for players to have well-developed aerobic fitness (aerobic performance -AP) (Modric et al, 2020a). Currently, it is generally accepted that well-developed AP helps soccer players maintain repetitive high-intensity actions in a soccer match, accelerate the recovery process, and maintain their physical condition at an optimum level during the entire game and season (Slimani et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that players regularly transit between brief bouts of high-intensity running and longer periods of low-intensity running [1,7]. These performances can be affected by different factors, such as the player's playing position in the game [8][9][10], physical capacities [7,11,12], tactical formations [13,14] and technical level [15]. In addition, contextual variables, such as the match status (win, draw, lose), location (home, away) and opponents' level (top, middle, bottom), impact the RP [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Such sessions included low-and moderate-speed running drills or low-demanding soccer drills that required total, low-, and moderate-intensity running, accelerations, and decelerations. Given the fact that these activities are related to the intensity of the aerobic threshold [37,38], constantly higher RTL of these variables (i.e., greater TDr, LIDr, ACCr and DECr on MD-5) probably allowed players to achieve a better adaptation of their aerobic capacities. Considering the fact that poor endurance preparation of players results in a rapid increase in fatigue, a greater number of errors, and more frequent loss of one-on-one plays [39], a better adaptation of the aerobic capacities during training will probably result in the ability to manage prolonged fatigue during the matches.…”
Section: Association Between Relative Training Load and Success In Soccermentioning
confidence: 99%